2024
DOI: 10.1590/1678-7757-2023-0219
|View full text |Cite
|
Sign up to set email alerts
|

In vitro characterization of a novel resin-based restorative material containing alkaline fillers

Matias Mederos,
Elisa de León,
Andrés García
et al.

Abstract: Objective: In this study, a comparative evaluation of the physicochemical properties of Cention N and other direct restorative materials was performed. Three restorative materials—a resin-modified glass ionomer (Fuji II LC), an alkasite-based resinous material (Cention N), and a resin composite (Tetric N Ceram)—were characterized in terms of degree of conversion, Knoop hardness number (KHN) ratio, flexural strength, elastic modulus, water sorption, water solubility, microshear bond strength to den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In that study, only the top surface of the light-cured specimens was evaluated, and the reported MH ratio was 48%, which was considerably lower compared to the MH ratios of the light-cured specimens obtained in our study (72–76%). Considering the methodological differences and the unknown material modifications that occurred during the development of Cention N, tested in the aforementioned study [ 33 ], to Cention Forte, which was tested in our study, it is not possible to discuss these differences in more detail.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In that study, only the top surface of the light-cured specimens was evaluated, and the reported MH ratio was 48%, which was considerably lower compared to the MH ratios of the light-cured specimens obtained in our study (72–76%). Considering the methodological differences and the unknown material modifications that occurred during the development of Cention N, tested in the aforementioned study [ 33 ], to Cention Forte, which was tested in our study, it is not possible to discuss these differences in more detail.…”
Section: Discussionmentioning
confidence: 97%
“…There is only one published study on ethanol softening of an early version of the alkasite material (Cention N) in which the Knoop hardness was compared after and before ethanol immersion to indirectly assess the crosslink density [ 33 ]. In that study, only the top surface of the light-cured specimens was evaluated, and the reported MH ratio was 48%, which was considerably lower compared to the MH ratios of the light-cured specimens obtained in our study (72–76%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation